Analisis Kecepatan (Speet) Pada Sprint 100 Meter Untuk peningkatan Peforma Atlet - Totonafo Hulu; Jan Revian Sidabalok; Kismiati Lovita Hutasoit; Jack Chris Saro Hia; Bryan Nickson Manurung; Mahmudin Matondang; Asep Prima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the foot movement patterns in the 100-meter sprint to enhance athlete performance, particularly during the initial acceleration phase. A descriptive qualitative method was employed with a 28-year-old sprinter who had competitive experience in the 100-meter sprint as the research subject. Data were collected through video recordings of the first 20 meters of the sprint track and observation sheets to assess biomechanical variables, including time, average speed, number and frequency of strides, stride length, knee and hip angles, as well as body posture. The results revealed that the athlete covered the first 20 meters in 3.93 seconds with an average speed of 5.04 m/s, completing 14 strides with an average stride length of 108.63 cm and a stride frequency of 3.33 strides/second. Biomechanical analysis showed a knee angle of 96.6°, a hip angle of 90.5°, and a body lean of 119.8°, all of which fall within the optimal range according to the literature. These findings indicate that the athlete’s acceleration performance is close to the semi-professional to professional sprinter standards; however, stride frequency improvement is still required to reach elite-level performance. This study highlights the importance of biomechanical-based technique evaluation to maximize sprint speed while minimizing the risk of injury.